The Effect of Quizizz Media on Learning Outcomes and Self-Confidence of Eighth Grade Mathematics Students Junior High School - Putri Anggraini; Isran Rasyid Karo-Karo (Plusminus: Jurnal Pendidikan Matematika, 2025)
Penelitian ini dilatar belakangi oleh rendahnya hasil belajar dan kepercayaan diri siswa dalam menjawab soal matematika. Tujuan penelitian ini untuk mengetahui pengaruh media interaktif berbasis Quizizz terhadap peningkatan hasil belajar dan kepercayaan diri siswa dalam menjawab soal matematika kelas VIII SMP Muhammadiyah 01 Medan Tahun Ajaran 2025/2026. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksperimen semu (quasi-experimental design) tipe pretest-posttest control group design. Sampel penelitian terdiri atas dua kelas, yaitu kelas eksperimen yang menggunakan media Quizizz dan kelas kontrol dengan pembelajaran konvensional, masing-masing berjumlah 30 siswa. Hasil penelitian ini menunjukkan bahwa nilai t hitung hasil belajar (2,737) dan kepercayaan diri (3,208) lebih besar dari t tabel (1,672), sehingga H₀ ditolak. Dengan demikian, media interaktif berbasis Quizizz berpengaruh signifikan terhadap peningkatan hasil belajar dan kepercayaan diri siswa menjawab soal matematika. This study was motivated by the low learning outcomes and self-confidence of students in answering mathematics questions. The purpose of this study was to determine the effect of Quizizz-based interactive media on improving learning outcomes and self-confidence of students in answering mathematics questions in grade VIII at SMP Muhammadiyah 01 Medan in the 2025/2026 academic year. This study used a quantitative approach with a quasi-experimental design, specifically a pretest-posttest control group design. The research sample consisted of two classes, namely the experimental class that used Quizizz media and the control class with conventional learning, each consisting of 30 students. The results of this study indicate that the calculated t-value for learning outcomes (2.737) and confidence (3.208) is greater than the t-table (1.672), so H₀ is rejected. Thus, Quizizz-based interactive media has a significant effect on improving students' learning outcomes and confidence in answering math questions.